Kajian Teknis Kinerja Jig Primer terhadap Kadar Recovery dan Looses Bijih Timah pada SHP KIP Mitra Matras di Bidang Pengolahan Mineral Unit Pengolahan PT Timah Tbk - Aditya, Ismu; Pitulima, Janiar; Andini, Delita Ega (MINERAL, 2024)
Bidang Pengolahan Mineral Processing Unit of PT Timah Tbk operates in the field of tin ore processing. The problem at the research location is that there is no standard operating standard for the Primary Jig tool for washing Processing Waste (SHP). The aim of this research is to determine the settings for the Primary Jig variables in order to obtain optimal levels, Sn recovery and looses. The research method used is Grafity Concentration. The feed used is SHP from KIP Mitra Matras. The experiment was carried out 21 times. Each experiment used 7 variations of Primary Jig stroke speed (300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm) and Bed thickness (70 mm, 80 mm, 90 mm). Grain Counting Analysis shows a feed Sn content value of 9.96%. GCA analysis shows that the minerals in the bait are cassiterite, ilmenite, monazite, zircone, pyrite, siderite, limonite, tourmaline, quartz and iron rust. Low stroke speed results in high concentrate Sn content with low Sn recovery and little looses wasted and vice versa. A high Bed thickness results in low Sn concentrate content, high Sn recovery, and a lot of looses is wasted, and vice versa. Setting the optimal Primary Jig operating variables with variations in punch speed of 450 rpm and Bed thickness of 80 mm obtained a Sn content of 41.36% and a Sn recovery of 60.11%. Based on the results of calculating the degree of liberation, the highest average value of the degree of liberation was obtained at mesh -100, indicating that the SHP KIP Mitra Matras concentrate is classified as having a fine grain size.